RIM‐binding proteins recruit BK‐channels to presynaptic release sites adjacent to voltage‐gated Ca2+‐channels - Sclip, Alessandra; Acuna Goycolea, Claudio; Luo, Fujun; Südhof, Thomas C. (The EMBO journal, 2018)
RIM‐binding proteins ensure coupling of BK‐channels to Ca2+ channels in the active zone to control neurotransmitter release.
Im Titel ist "2+" hochgestellt
Gesehen am 04.09.2019